PENGARUH PELAYANAN PUBLIK TERHADAP TINGKAT KEPUASAN MASYARAKAT DI DISTRIK ABEPURA KOTA JAYAPURA - Usman, Syamsudin (DINAMIS, 2023)
Public service is an activity aimed at meeting the community's needs by applicable regulations for citizens and residents. This includes the provision of goods, services, and administration by government agencies. Fair and accountable public services are essential to build public trust, with public service ethics as its primary foundation. This research focuses on the reality and expectations related to public services in Abepura District, Jayapura City. The research approach used is quantitative. The results of the study indicate that, overall, the level of satisfaction with public services provided by officials in Abepura District is quite adequate. However, there still needs to be a gap in the community's perception of these services. Although perceived as quite good, they must still fully meet the community's expectations. Thus, this research highlights the need to improve the provision of more holistic and practical public services, which would better and more comprehensively meet the community's expectations and needs in the future.